Brainstem Evoked Potential Indices of Subcortical Auditory Processing Following Mild Traumatic Brain Injury - Vander Werff, Kathy R. (Ear Hear, 2017)
OBJECTIVES: The primary aim of this study was to assess subcortical auditory processing in individuals with chronic symptoms following mild traumatic brain injury (mTBI) by measuring auditory brainstem responses (ABRs) to standard click and complex speech stimuli. Consistent with reports in the literature of auditory problems following mTBI (despite normal hearing thresholds), it was hypothesized that individuals with mTBI would have evidence of impaired neural encoding in the auditory brainstem compared to non-injured controls, as evidenced by delayed latencies and reduced amplitudes of ABR components. We further hypothesized that the speech-evoked ABR would be more sensitive than the click-ABR to group differences due to its complex nature, particularly when recorded in a background noise condition. DESIGN: Click- and speech-ABRs were collected in 32 individuals diagnosed with mTBI in the past 3–18 months. All mTBI participants were experiencing on-going injury symptoms for which they were seeking rehabilitation through a brain injury rehabilitation management program. The same data were collected in a group of 32 age- and gender-matched controls with no history of head injury. ABRs were recorded in both left and right ears for all participants in all conditions. Speech-ABRs were collected in both quiet and in a background of continuous 20-talker babble ipsilateral noise. Peak latencies and amplitudes were compared between groups, and across subgroups of mTBI participants categorized by their behavioral auditory test performance. RESULTS: Click-ABR results were not significantly different between the mTBI and control groups. However, when comparing the control group to only those mTBI subjects with measurably decreased performance on auditory behavioral tests, small differences emerged including delayed latencies for waves I, III, and V. Similarly, few significant group differences were observed for peak amplitudes and latencies of the speech-ABR when comparing at the whole group level but were again observed between controls and those mTBI subjects with abnormal behavioral auditory test performance. These differences were seen for the onset portions of the speech-ABR waveforms in quiet, and were close to significant for the onset wave. Across groups, quiet vs. noise comparisons were significant for most speech-ABR measures but the noise condition did not reveal more group differences than speech-ABR in quiet, likely due to variability and overall small amplitudes in this condition for both groups. CONCLUSIONS: The outcomes of this study indicate that subcortical neural encoding of auditory information is affected in a significant portion of individuals with long-term problems following mTBI. These subcortical differences appear to relate to performance on tests of auditory processing and perception, even in the absence of significant hearing loss on the audiogram. While confounds of age and slight differences in audiometric thresholds can’t be ruled out, these preliminary results are consistent with the idea that mTBI can result in neuronal changes within the subcortical auditory pathway that appear to relate to functional auditory outcomes. Although further research is needed, clinical audiological evaluation of individuals with ongoing post-mTBI symptoms is warranted for identification of individuals who may benefit from auditory rehabilitation as part of their overall treatment plan.